2004
DOI: 10.1086/425517
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Influenza Vaccination Influences Mucosal and Systemic T Cell–Mediated Immunity in Healthy Adults

Abstract: We sought to determine whether palatine tonsils (PTs) harbor naturally acquired influenza-specific T cell immunity and whether routine parenteral immunization with influenza vaccine influences mucosal and systemic T cell reactivity. We demonstrate that tonsillar and peripheral blood mononuclear cells (PBMCs) proliferate strongly to influenza antigens, suggesting that naturally acquired immunity exists within both the mucosal and systemic compartments. Influenza vaccination induced significantly stronger T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…The current licensed influenza vaccine confers protection by inducing a prophylactic antibody response against the virus. There is evidence the vaccine also induces a specific T cell response [15]; however, several studies have shown that this response is significantly impaired in the elderly [16] and does not increase significantly the number of influenza-specific IFN-c-producing T cells in the general adult population [17]. Moreover, most T cell epitopes in influenza are found in its internal proteins, and the nature of the current vaccine preparation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The current licensed influenza vaccine confers protection by inducing a prophylactic antibody response against the virus. There is evidence the vaccine also induces a specific T cell response [15]; however, several studies have shown that this response is significantly impaired in the elderly [16] and does not increase significantly the number of influenza-specific IFN-c-producing T cells in the general adult population [17]. Moreover, most T cell epitopes in influenza are found in its internal proteins, and the nature of the current vaccine preparation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1, A-D and H). Depletion of CD19 ϩ cells also revealed a smaller proliferative response to Nl OMV that typically peaked later at days 4 -9, which is characteristic of cognate T cell proliferation (16,31) (Fig. 1C).…”
Section: Low-level Mucosal T Cell Memory To Nl Omv During the Peak Agmentioning
confidence: 91%
“…Responses to flu were measured as a positive control because the majority of children have been primed as a result of natural infection by influenza virus by 3 years of age (30). In addition, we have previously demonstrated flu-specific T cell responses in the PT over a wide range of ages (31).…”
Section: Low-level Mucosal T Cell Memory To Nl Omv During the Peak Agmentioning
confidence: 99%
See 1 more Smart Citation
“…vaccination with an inactivated virus (62). Another study found that parenteral immunization with influenza vaccine in humans could induce both systemic immunity (anti-influenza Ab in serum and Ag-specific CD4 ϩ T cells in PBMC) as well as IgA Abs in saliva and IFN-␥-secreting T cells in palatine tonsils (63). FluMist is the first live attenuated influenza vaccine and also the first nasally administered vaccine to be marketed in the United States for the prevention of flu in individuals 2-49 years of age (64).…”
Section: The Prospect Of Mucosal Vaccines For Influenzamentioning
confidence: 99%